MATHEMATICAL LEARNING OF STUDENTS WITH ASD: A REVIEW IN LIGHT OF SEMIOTIC REPRESENTATION REGISTERS (Interdisciplinary Studies Journal, 2025)
This Systematic Literature Review (RSL) investigated the mathematical learning of students with Autism Spectrum Disorder (ASD) in the early years of Elementary School. The study focused on Raymond Duval's Serious Representation Records (TRRS), analyzing dissertations and thesis work from the Theses and Dissertations Catalog the CAPES aiming to understand how the mobilization of semiotic representation records by these students occurs. According to the TRRS, the conversion between different records is crucial because it leads to coordination (autonomy). For students with ASD, mediation is not only necessary, but fundamental, because it helps in the development of the skill, due to the difficulties of the spectrum in activities linked to the focus. Mediation may involve instruments, strategies, practical activities or teaching support. The results of the RSL  showed that the mobilization of records happens successfully when mediated, being mediation by games, by technologies and teaching mediation more recurrent and effective. Mediation allows, therefore, the conquest of autonomy by students with ASD, to solve maternal issues, which extends beyond school walls.
Keywords: Autismo Spectrum Discorde; Math learning; Teor off Semiótica Representativo Registres; Raymond Duval; Mediastino